2000
DOI: 10.1034/j.1600-0463.2000.d01-48.x
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus induces apoptosis in the hematopoietic cell line MO7e

Abstract: Several studies have shown that human cytomegalovirus (HCMV) induces growth suppression of hematopoietic progenitors. In vitro studies have demonstrated that the HCMV-induced suppression is independent of viral protein production. Previous studies have indicated a link between HCMV infection and apoptosis in human cells. The purpose of our study was to investigate whether the observed inhibitory effect of HCMV on the human myeloid progenitors could be connected to the induction of apoptosis. The growth and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Moreover, MCMV induces apoptosis in uninfected neuronal cells in vivo (30), but not in in vitro culture (30). In addition, HCMV has been reported to induce apoptosis in hematopoietic progenitor MO7 cells (51). Clearly the capacity of HCMV to block or even induce apoptosis in infected cells may be dependent on the stage of differentiation, cells of different origins and/or different culture conditions, and the virus strains involved.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MCMV induces apoptosis in uninfected neuronal cells in vivo (30), but not in in vitro culture (30). In addition, HCMV has been reported to induce apoptosis in hematopoietic progenitor MO7 cells (51). Clearly the capacity of HCMV to block or even induce apoptosis in infected cells may be dependent on the stage of differentiation, cells of different origins and/or different culture conditions, and the virus strains involved.…”
Section: Discussionmentioning
confidence: 99%
“…HCMV can induce growth suppression of hematoietic progenitors possibly via apoptosis [4,14]. Our group has reported that HCMV can directly infect both primary cultured CD34 ?…”
Section: Introductionmentioning
confidence: 98%
“…Conversely, apoptosis plays an important role in the dissemination and pathogenesis of several viral infections. HCMV can induce apoptosis in several cell types through different mechanisms that may favor either viral clearance or disease development [4,[8][9][10]. Recent studies have suggested that viral infections may be modulated by mitogenactivated protein kinase pathways [11,12].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…21 Under certain circumstances, CMV infection may even directly induce apoptosis and growth suppression, as shown for hematopoetic progenitors. 22 …”
Section: Mechanistic Considerationsmentioning
confidence: 99%